(untitled) (Indian Journal of Arid Horticulture, 2025)
Grape is a highly perishable fruit and can not be stored for longer time under ambient conditions. Many workers had tried to increase its shelf-life by pre-cooling, fumigation, pre and post-harvest chemical treatments, packaging, controlled atmosphere and cold storage which are reviewed in this paper.